COMPARING INFLUENZA POSITIVITY RATES BY REAL-TIME RT-PCR, ELISA AND VIRAL CULTURE METHODS IN CÔTE D’IVOIRE, WEST AFRICA, IN 2009 - Talla Nzussouo, Ndahwouh; Adje Kadjo, Herve; Coulibaly, Daouda; Ekaza, Euloge; Kouakou, Bertin; Coulibaly N'Golo, David; Tempia, Stefano; Davis, Richard; Dosso, Mireille; Thompson, Mark (African Journal of Infectious Diseases (AJID), 2013)
Detection of circulating influenza strains is a key public health concern especially in limited-resource settings where diagnosis capabilities remain a challenge. As part of multi-site surveillance in Côte d’Ivoire during the 2009 influenza A(H1N1) pandemic, we had the opportunity to test respiratory specimens collected from patients with acute respiratory illness (ARI). We analyzed and compared the percentage of specimens testing positive using three laboratory methods (rtRT-PCR, ELISA, viral culture). From January to October 2009, 1,356 respiratory specimens were collected from patients with acute respiratory illness and shipped at the WHO NIC (Institut Pasteur) Cote d’Ivoire, and 453 (33%) tested positive for influenza by one or more laboratory methods. The proportion of positive influenza tests did not differ by the sex or age of the patient or presenting symptoms, but did differ depending on the timing and site of specimen collection. Of the 453 positive specimens, 424 (93.6%) were detected by PCR, 199 (43.9%) by ELISA and 40 (8.8%) by viral culture. While seasonal influenza A(H1N1) virus strains were prominent, only four 2009 pandemic influenza A(H1N1) cases were detected. Use of molecular biology method (rtRT-PCR) increased sensitivity and diagnosis capabilities. Among all three methods used, rRT-PCR was the most sensitive and rapid method. More capacity building is still required for viral culture. Need to collect denominator data in order to have an accurate estimate of the burden of influenza. There was delayed introduction of pandemic influenza A(H1N1)2009 in Cote d’Ivoire